Studies on Mechanical Washing of Ginger Rhizomes - Jayashree, E; Visvanathan, R (Journal of Agricultural Engineering, 2010)
Experiments on washing of ginger rhizomes in a rotary mechanical vegetable washer were conducted at three peripheral washing drum speeds of 2.83, 3.45 and 4.08 m.s?¹ for three varying washing durations of 5, 10 and 15 min. The performance of ginger washer was evaluated based on bruise index, mechanical washing efficiency, microbial washing efficiency and colour of washed ginger. For microbial washing efficiency to be above 80%, washing speed of 3.45 m.s?¹ for 5 min duration corresponding to microbial washing efficiency of 92% was considered as optimum. At the optimum washing condition, the bruise index and mechanical washing efficiency were 7.5% and 97.8%, respectively. The colour values ‘L’, ‘a’ and ‘b’ of ginger washed at optimized conditions were 46.34, 7.44 and 18.71, respectively. The capacity of the mechanical washer was found to be 60 kg.h?¹ of fresh ginger.